2017
DOI: 10.1103/physrevd.95.026008
|View full text |Cite
|
Sign up to set email alerts
|

One-loop tests of the supersymmetric higher spin AdS4/CFT3 correspondence

Abstract: We compute one loop free energy for D = 4 Vasiliev higher spin gravities based on Konstein-Vasiliev algebras hu(m; n|4), ho(m; n|4) or husp(m; n|4) and subject to higher spin preserving boundary conditions, which are conjectured to be dual to the U (N ), O(N ) or U Sp(N ) singlet sectors, respectively, of free CFTs on the boundary of AdS 4 . Ordinary supersymmetric higher spin theories appear as special cases of Konstein-Vasiliev theories, when the corresponding higher spin algebra contains OSp(N |4) as subalg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
(103 reference statements)
0
17
0
Order By: Relevance
“…First, utilizing the results derived in [33][34][35], one can check that the bulk free energy at one-loop is free of UV divergence [33][34][35]. The coefficient of the log M term also agrees with the expectation from [36], which states that each bulk spin-1 gauge fields obeying the mixed boundary condition contribute to the one loop free energy of the Vasiliev theory by −(1/2) log M .…”
Section: Jhep11(2017)190mentioning
confidence: 54%
See 1 more Smart Citation
“…First, utilizing the results derived in [33][34][35], one can check that the bulk free energy at one-loop is free of UV divergence [33][34][35]. The coefficient of the log M term also agrees with the expectation from [36], which states that each bulk spin-1 gauge fields obeying the mixed boundary condition contribute to the one loop free energy of the Vasiliev theory by −(1/2) log M .…”
Section: Jhep11(2017)190mentioning
confidence: 54%
“…Hence we regard our result as prediction to the on-shell action of the N = 5 Vasiliev theory in AdS 4 . As mentioned above, the second term agrees with the one-loop free energy of the Vasiliev theory on AdS 4 , which is free of logarithmic divergences [33][34][35] and equal to (−1/2) times the number of bulk spin-1 gauge fields obeying the mixed boundary condition [36]. In section 6, we summarize and discuss possible extensions of this work.…”
Section: Jhep11(2017)190mentioning
confidence: 61%
“…Moreover, the CIRZ allowed to tackle the one-loop free energy computation of the stringy AdS theory dual to free matrix model CFTs in the N → ∞ limit [14,[18][19][20]. The CIRZ also proved useful in other vector model dualities: the "colored" higher-spin gravity (where the four-dimensional CIRZ was generalized to fermionic fields) [21] and the type-J higherspin theories (whose conjectured dual are free vector model based on a massless spin-j field) [22]. Some key elements of the CIRZ were also used in [23].…”
Section: Contentsmentioning
confidence: 99%
“…(4.39) By setting ǫ = +1 or −1, we obtain the formulae derived in [14] and [21] for bosonic and fermionic spectrum, respectively. To compute the secondary contribution, we need the first derivative of µ ǫ,n (z, β):…”
Section: Adsmentioning
confidence: 99%
“…Although one of the appealing features of higher-spin holography is the fact that these dualities do not require supersymetry, the four dimensional higher-spin gravity admits a supersymmetric extension with arbitrary N : see [54] for a review (as well as the recent paper [55] where several one-loop tests of these extensions were performed, together with [26] for the 6-dimensional case). Supersymmetric higher-spin algebras 7 were studied in four dimensions in [43,46,57], an analysis later extended to any dimension in [8], where it was also shown that the spectrum of these supersymmetric higher-spin theories is given by the tensor product of the direct sum of the Rac and Di singletons (possibly decorated with Chan-Paton factor, that we will not consider here).…”
Section: Type Abmentioning
confidence: 99%